Analisis Ekuitas Merek - Ali Hasan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2010)
Brand equity continues to be one of the critical areas for marketing. This research explores some of the consequences attributes may have on brand equity such as the bias on consumer preference. For comparative purposes, this research is conducted on the high involvement using on the four soft drinks brands. This research being measured the impact of attributes preferences and actual choice frequency for brand attributes on brand equity. Attributes are examined from a tangible and intangible perspective and both are found to be important contributors to brand equity and brand choice.